THE INFLUENCE OF CLASSROOM MANAGEMENT ON LEARNING OUTCOMES CLASS V STUDENTS OF STATE PRIMARY SCHOOL NO. 066654 KELAMBIR V TANJUNG GUSTA DISTRICT MEDAN HELVETIA DISTRICT - Taruli Marito Silalahi, Asa'aro Laia, Nanda Ayu Setiawati, Fitriani Sinaga (Pusdikra-Publishing.com, 2020)
This research aims to find out whether the better the classroom management carried out by the teacher, the better the learning outcomes of class V students at State Elementary School No. 066654 Kelambir V, Tanjung Gusta Village, Medan Helvetia District. This research is quantitative research with an ex post facto type of research. The researcher did not carry out any treatment on the research subjects, the researcher only wanted to know the responses that the research subjects had related to the Influence of Class Management on the Learning Outcomes of Class V Students at State Elementary School No. 066654 Kelambir V, Tanjung Gusta Village, Medan Helvetia District. The population in this study were students of Class VA and VB at State Elementary School No. 066654 Kelambir V, totaling 56 students. There are two variables studied in this research, namely classroom management and student learning outcomes. Data taken through questionnaires and documentation. Data analysis uses Simple Linear Regression analysis. Based on the results of the analysis using SPSS, a person correlation value of 0.716 was obtained, meaning that there is a significant relationship between classroom management and student learning outcomes in the strong relationship category. Meanwhile, the significant value is 0.000 for class management (X) and for learning outcomes data (Y) whose value is smaller than 0.05, meaning there is a relationship between class management (X) and learning outcomes (Y).